Consequences of not-shaking and shake-fire delays on the emitted dose of some commercial solution and suspension pressurized metered dose inhalers. (2nd July 2020) - Chierici, Veronica; Cavalieri, Luca; Piraino, Alessio; Paleari, Davide; Quarta, Eride; Sonvico, Fabio; Melani, Andrea S; Buttini, Francesca
ABSTRACT: Background: Pressurized metered-dose inhalers (pMDIs) include hydrofluoroalkane (HFA) propellant to generate a drug aerosol upon actuation and drugs can be formulated as solution or suspension. Suspended particles can cream or sediment depending on density differences between drug and propellant and shaking the pMDI is an essential step to ensure a uniform drug dose release. Research design and methods: The effect of the delay (0, 10, 30, 60 seconds) in pMDI actuation after shaking and the effect of no-shaking during the canister life on the emitted dose (ED) for commercial solution and suspension pMDIs was investigated. Results: The ED for solutions was unaffected by no-shaking or by the progressive increasing delay in actuation after shaking (between 77% and 97%). For all the suspension products, shaking was demonstrated to be critical to assure the close to nominal drug delivery. In detail, the actuation delay after shaking led to an increase up to 380% or a drop to 32% of ED in relation to the label claim with high variability. Conclusion: The drug delivered can vary widely for no-shaking and over different shake-fire delays with suspension pMDIs while solution formulations appear to remain stable.